Exploring the influence of counterpart materials on tribological behaviors of epoxy composites. (November 2016) - Qi, Huimin; Zhang, Ga; Wetzel, Bernd; Österle, Werner; Wang, Tingmei; Wang, Qihua
Abstract: The dependence of the friction and wear of epoxy (EP) composites materials on counterpart materials, such as standard bearing steel, medium carbon steel and chrome-plating (Cr), was investigated. The conventional composite filled with short carbon fiber (SCF) and graphite shows the highest tribological performance when rubbing against Cr, whereas, the hybrid nanocomposite (EP filled with SCF, graphite and silica nanoparticles) exhibits the lowest friction and wear when sliding against the standard bearing steel. The role of nanoparticles in the tribological performance is distinctly different when sliding against with various counterpart materials. It is demonstrated that counterpart materials exert an important influence on material transfer, tribo-oxidation and mechanical mixing of wear products, resulting in the different formation mechanisms of transfer film. Highlights: Counterpart materials exert an important influence on the tribological performance of epoxy composites. Variation of counterpart materials leads to distinctly different transfer film structures. A close relationship between the tribological behaviors and transfer film structures was revealed.